2013
DOI: 10.1128/aem.00777-13
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Salmonella Populations from Biological, Chemical, and Physical Indicators in Florida Surface Waters

Abstract: c Coliforms, Escherichia coli, and various physicochemical water characteristics have been suggested as indicators of microbial water quality or index organisms for pathogen populations. The relationship between the presence and/or concentration of Salmonella and biological, physical, or chemical indicators in Central Florida surface water samples over 12 consecutive months was explored. Samples were taken monthly for 12 months from 18 locations throughout Central Florida (n ‫؍‬ 202). Air and water temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
107
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(138 citation statements)
references
References 35 publications
28
107
2
Order By: Relevance
“…Conversely, a survey of Canadian rivers reported significantly higher prevalence in spring than in summer, although seasonal precipitation was also correlated with increased Salmonella presence (43). Moreover, results showing small but significant positive correlations with temperatures and rainfall are consistent with prior research for central Florida surface water during an overlapping time period (16). Although regression analysis provided predictive models for effects of rainfall and temperature on Salmonella densities, further study is needed to refine these models for evaluating Salmonella risk.…”
Section: Figsupporting
confidence: 73%
See 4 more Smart Citations
“…Conversely, a survey of Canadian rivers reported significantly higher prevalence in spring than in summer, although seasonal precipitation was also correlated with increased Salmonella presence (43). Moreover, results showing small but significant positive correlations with temperatures and rainfall are consistent with prior research for central Florida surface water during an overlapping time period (16). Although regression analysis provided predictive models for effects of rainfall and temperature on Salmonella densities, further study is needed to refine these models for evaluating Salmonella risk.…”
Section: Figsupporting
confidence: 73%
“…Multiple linear regression modeling revealed that generic E. coli levels and temperatures in both water and sediment were significantly related to the Salmonella densities (P Ͻ 0.05). However, the R 2 values of these models were low (Ͻ0.2), indicating that the models did not reveal strong linear relationships (16). Therefore, logistic regression models were also used to examine Salmonella occurrence with respect to these parameters, and a predictive relationship (P Ͻ 0.05) was observed for both generic E. coli densities and water temperatures (not shown) relative to Salmonella densities in water and sediment samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations